Analyzing the Prevalence of Dengue Fever and Its Environmental Determinants in Urban and Rural Areas of South Sulawesi - Indria, Izza; Qalbi , Ummul; Agustina, Aulia (ScieClouds Publishing, 2024)
Dengue fever continues to be a vital health risk that affects people in South Sulawesi's tropical areas along with other regions. This research investigated dengue fever prevalence rates together with their environmental risk factors between urban and rural settings through a quantitative cross-sectional research design. A total of 350 households participated in the study with 175 in urban areas and 175 in rural areas. The researchers used structured questionnaires together with official health records and field observations to collect the data. This research applied logistic regression along with ANOVA and Pearson correlation techniques to evaluate important determinants as well as identify environmental differences between the urban and rural zones. The study revealed that urban population experienced a higher occurrence of dengue fever with rates at 27% whereas the rural population reported 16% cases. Risk factors associated with uncovered water containers in addition to poor waste management and high population density defined urban settings however rural areas experienced dense vegetation and inadequate waste disposal approaches. Research findings demonstrated that stagnant water (p0.001) together with poor waste management (p0.001) and vegetation density (p0.005) created statistical links to dengue prevalence. The research completes missing knowledge by showing different transmission factors between distinct geographical areas through direct comparison of urban versus rural patterns. This study demonstrates why public health intervention needs such specific methods. The focus of urban intervention programs should be waste management along with mosquito breeding site control yet rural intervention strategies need to focus on vegetation management coupled with better healthcare accessibility.